PROGRAM PENINGKATAN PEMASARAN HASIL PERTANIAN MELALUI DIGITALISASI DI DESA KRETEK, KECAMATAN TAMAN KROCOK, KABUPATEN BONDOWOSO - Romansa, Deta Safa; Primasari, Cerisa Cantika; Sabrina, Laurentcya Kayla; Aprilia, Ruth; Hasan, Saiful (Jejaring Penelitian dan Pengabdian Masyarakat, 2023)
Kretek Village is a village where the majority of its inhabitants work as farmers. Agriculture plays a vital role in the global economy, and effective marketing is key to enhancing farmers' income and meeting the growing consumer demand. In an effort to address traditional marketing challenges and harness the potential of digital technology, a community engagement program has been implemented to enhance the marketing of agricultural products through digitalization. This program aims to empower farmers to leverage digital technology to optimize the marketing of their agricultural products. The outcomes of this program are expected to enable farmers, who typically market their products only to middlemen, to access broader markets and significantly increase sales opportunities. The success of this program underscores the positive potential of digitalization in strengthening the agricultural value chain and improving the welfare of farmers. However, challenges related to technological accessibility and infrastructure limitations also need to be considered. Therefore, sustainable measures have been recommended to ensure the continuity of this program and to expand its impact.